Progressive Collapse Resilience of Concrete Structures: Mechanisms, Simulations and Experiments - Qian, Kai.; Fang, Qin. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
The book introduces the comprehensive analysis methodology regarding progressive collapse, and the critical issues may happen in concrete structures. Main topics include: the influential parameters of the development of the main load-resisting mechanisms; the dynamic effects with sudden column removal scenarios; the contribution of non-structural components to improve the resilience of concrete structures; uncertainties in progressive collapse analysis. Based on the empirical research of the author and his team, the book provides valuable knowledge in the field of progressive collapse and bridges the gap between academic research and practice.
Chapter 1. Introduction -- Chapter 2. Mechanisms of progressive collapse of concrete structures -- Chapter 3. Dynamic increase factor (DIF) of concrete structures -- Chapter 4. Spatial and slab effects on concrete structures -- Chapter 5. Mechanisms of progressive collapse of flat slab structures -- Chapter 6. Performance of infilled frames during progressive collapse -- Chapter 7. Vulnerability and robustness of RC frames to resist progressive collapse.
Keywords: Geotechnical engineering; Buildings -- Design and construction; Engineering geology; Geotechnical Engineering and Applied Earth Sciences; Building Construction and Design; Geoengineering